2014
DOI: 10.1103/physreve.90.030201
|View full text |Cite
|
Sign up to set email alerts
|

Armoring a droplet: Soft jamming of a dense granular interface

Abstract: Droplets and bubbles protected by armors of particles have found vast applications in encapsulation, stabilization of emulsions and foams, or flotation processes. The liquid phase stores capillary energy, while concurrently the solid contacts of the granular network induce friction and energy dissipation, leading to hybrid interfaces of combined properties. By means of nonintrusive tensiometric methods and structural measurements, we distinguish three surface phases of increasing rigidity during the evaporatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…Finally, we remind that we used the surface tension of the solution in Eq.5 rather than an effective surface tension despite the presence of particles on the interfaces. It has been shown that, when adsorbed at an interface, nanoparticles as well as microparticles can change the surface tension of the particle laden interface they are attached to [35][36][37]. This change becomes significant at high surface coverage (∼ 0.8) and might thus be one of the causes of deviation from Taylor-Culick law that we observe.…”
Section: In This Case ∆Eamentioning
confidence: 52%
See 1 more Smart Citation
“…Finally, we remind that we used the surface tension of the solution in Eq.5 rather than an effective surface tension despite the presence of particles on the interfaces. It has been shown that, when adsorbed at an interface, nanoparticles as well as microparticles can change the surface tension of the particle laden interface they are attached to [35][36][37]. This change becomes significant at high surface coverage (∼ 0.8) and might thus be one of the causes of deviation from Taylor-Culick law that we observe.…”
Section: In This Case ∆Eamentioning
confidence: 52%
“…where (A; B) = (1 ; 4 3 ) for BL films and (A; B) = (1 − φ; 2 3 ) for ML films. The value of the parameter B in the monolayer configuration is half its value in the bilayer configuration because the particles are attached to the two liquid/air interfaces of the film, so for each interface, we count half the particle mass .…”
Section: In This Case ∆Eamentioning
confidence: 99%
“…One consequence of this microscopic behavior is that the shell resistance departs strongly from what is expected from elasticity, contrary to what is commonly assumed [16,40,41]. This suggests ways to reinforce the colloidal armor by inhibiting the short-wavelength dislocations, for example, by using nonspherical or rough particles to prevent rolling or by using adhesive particles to sinter the shell.…”
Section: Discussionmentioning
confidence: 90%
“…One way to understand the underlying mechanisms is to focus on the behavior of a single particle-covered liquid-air interface. However, the difficulty of making quantitative measurements on a single coated bubble implies that most of the work was done by using mm-scale liquid droplets, as surrogate systems for air bubbles [12][13][14][15][16][17][18], and aspirating these droplets or letting them evaporate while observing a range of behaviors, depending on the experimental setup. In contrast, experiments using air bubbles, which have shown the arrest of gas dissolution in the liquid, remain mostly qualitative [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…The connement of particles on the surface of a liquid marble allows surface tension to provide a two-dimensional isotropic compressive stress and this can cause a jamming transition and shear-induced liquid-solid transitions leading to close-packed "armoured" droplets. 86 This transition from capillary-like to jammed granular-like phases as particle surface fractions on liquid marbles increase has been discussed by Lagubeau et al 87 By following the shape and grain network organization of slowly evaporating liquid marbles they identi-ed three shell phases: liquid-like (L), so-jammed solid (S 1 ) and hard-jammed solid (S 2 ). They suggested the L-phase represented the liquid marbles rst reported by Aussillous & Quéré 1 with a cohesion-dominated loose structure stabilized by capillary interaction and having a shape determined by a Laplacetype law with a reduced surface tension.…”
Section: Phases Of Particle Monolayersmentioning
confidence: 86%